The Relationship between Community Trust and Traditional Medicine in the Karang Tengah Health Center Working Area - Muhammad Irsal Fatahillah; Hendri Hadiyanto; Hadi Abdillah (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2026)
This study aimed to analyze the relationship between community beliefs and the use of traditional medicine in the working area of Karang Tengah Health Center, Sukabumi. This study used a quantitative research design with correlational analytic method and cross-sectional approach. A total of 99 respondents were selected using accidental sampling technique from a population of 20,790. Primary data were collected through a questionnaire that evaluated the community's belief in traditional medicine as well as the frequency of its use, while secondary data were obtained from the annual report of the puskesmas and official sources of the Ministry of Health. Data were analyzed using the Chi-Square test to measure the relationship between variables. The results showed that the majority of respondents had a high level of trust in traditional medicine (43.4%) and most used traditional medicine at a moderate level (44.4%). Bivariate analysis revealed a significant association between the level of trust and the use of traditional medicine with a p value of <0.05. Factors such as bad experiences with modern medicine, socio-cultural influences, and more affordable costs encourage people to choose traditional medicine. This study concludes that people's trust significantly influences their decision to use traditional medicine. These results are expected to contribute to the development of more inclusive health policies by effectively integrating traditional and modern medicine